PENGARUH KONFLIK PERAN, KELEBIHAN PERAN, INDEPENDENSI, DAN KOMPETENSI TERHADAP KINERJA AUDITOR DENGAN KECERDASAN SPIRITUAL SEBAGAI VARIABEL MODERASI (Studi Empiris pada Kantor Akuntan Publik Pekanbaru dan Padang) - Endah Aprimulki; Kamaliah '; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study examine the influence of role conflict, role overload, independency, and competency to auditor performance with spiritual intelligense as moderating variable (Empirical Study on Representation of Auditor at Pekanbaru and Padang. Respondents in this study are auditors who worked public accounting firm in Pekanbaru and Padang. The number of auditor that were visited in this study were 60 auditors from 12 public accounting firms. The method of determining the sample is by using purposive sampling method, while the data processing method used by reseacher are the multiple regression and moderate regression analysis and use SPSS version 20.00 as the software for processing the data. The result shows that the role conflict give a significant influence in auditors performance. Variable of role overload give a significant influence in auditors performance. Variable of independency give a significant influence in auditors performance. Variable of competency give a significant influence in auditors performance. Spiritual intelligent as moderating variable can moderate role conflict, role overload, independency, and competency on auditors performance.Keyword : role conflict, role overload, independency, competency, spiritual intelligence, auditor performance